Algorithm for multi-board radio-electronic devices synthesis on maximal accepted overheat - Sinotin, A.M.; Tsymbal, O.M.; Kolesnikova, T.A.; Sotnik, S.V. (Radiotekhnika, 2017)
The provision of a normal thermal regime for the future design of the radio-electronic device at the design stage prior to its manufacture is considered. The effect of the form of the radio electronic device on its temperature regime at the stage of its design is established. Tha algorithm for the thermophysical design of single-unit radioelectronic devices has been developed. For the first time recommendations were received on the choice of the optimal form of the radio electronic device at the design stage prior to its manufacture.